Exploring the impact of the COVID-19 pandemic on approaches to innovation in the consulting industry: a grounded theory pilot study - Diane Laurette Kamning (Innovation & Management Review)
Purpose – There is a significant pressure on consulting businesses to produce innovative solutions and to assist their clients in producing innovative solutions for their organizational problems as well. In addition to that challenging need to innovate for survival and competition, as other contemporary firms, consultancies must face the global changes brought by the outbreak of the coronavirus infection since 2019. This qualitative pilot study aimed at exploring the impact of the coronavirus disease 2019 (COVID-19) pandemic on the approaches to innovation in the consulting industry. Design/methodology/approach – Triggered from the literature gap on approaches to innovation in consultancies during the unprecedented COVID-19 pandemic, a grounded theory approach was used to generate a theoretical explanation of how the COVID-19 is affecting the strategies and approaches of businesses in harnessing innovation opportunities from the perspectives of four professionals from an information technology (IT) consultancy in the USA. Findings – The findings of this pilot study showed that organizational leaders' increased responsiveness, a Job-To-Be-Done strategy, organizational support and team adaption are the keys to harvesting dynamic capabilities for better competition, even during global environmental changes. Practical implications – This implies that managers remain the main actors in a firm's efforts to harvest dynamic capabilities. Innovation strategists, business leaders and policymakers can confidently work together to implement novel and flexible work settings that integrate both social and economic advancements. Originality/value – Theoretical implications support the sustainable innovation strategy concepts and the Job-To-Be-Done theory. Finally, the substantive theory from this pilot study lays the ground for future research on approaches to innovation in the consulting industry.